The Personalization Privacy Paradox: An Empirical Evaluation of Information Transparency and the Willingness to be Profiled Online for Personalization1 - Awad, Naveen Farag; Krishnan, M. S. (MIS Quarterly, 2006)
Firms today use information about customers to improve service and design personalized offerings. To do this successfully, however, firms must collect consumer information. This study enhances awareness about a central paradox for firms investing in personalization; namely, that consumers who value information transparency are also less likely to participate in personalization. We examine the relationship between information technology features, specifically information transparency features, and consumer willingness to share information for online personalization. Based on a survey of over 400 online consumers, we examine the question of whether customer perceived information transparency is associated with consumer willingness to be profiled online. Our results indicate that customers who desire greater information transparency are less willing to be profiled. This result poses a dilemma for firms, as the consumers that value information transparency features most are also the consumers who are less willing to be profiled online. In order to manage this dilemma, we suggest that firms adopt a strategy of providing features that address the needs of consumers who are more willing to partake in personalization, therefore accepting that the privacy sensitive minority of consumers are unwilling to participate in personalization, despite additional privacy features.